Analisis Produksi Program Khazanah Trans7 Episode Khazanah Etalase - Diniah, Zouhrotun; Syarah, Maya May (KOMUNIKA, 2019)
The purpose of this research based on the problem statement was to find out the program format used by the Khazanah Trans7 program on the Khazanah Etalase episode and find out the Khazanah Trans7 production process on the Khazanah Etalase episode in terms of preproduction, production, and postproduction. The research method used in this study is a qualitative approach with an observation method. The author conducts direct research in the field to find out how the production process of the Khazanah Trans7 program. The results of observations, interviews, and documentation in this study can be concluded that the Khazanah Trans7 Episode showcase program uses a heterogeneous type of Magazine program. For the production process, namely, preproduction reporters look for themes then presented in pitching then writing the script. Furthermore, the production is to change the script into visual audio starting from visual pitching, filming, transferring image files, editing scripts and voice over. After the production process is finished entering the post- production stage, the final process is to combine all the material to be ready to broadcast with several processes including the collection of all material, image editing, editing voice over, titling, mixing, review, quality control, and mastering and then ready to air.AbstrakTujuan dari penelitian ini berdasarkan pernyataan masalah adalah untuk mengetahui format yang digunakan oleh program Khazanah Trans7 pada Episode Khazanah Etalase dan untuk mengetahui proses produksi dalam hal praproduksi, produksi dan pascaproduksi. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik pengambilan data observasi. Penulis melakukan penelitian langsung di lapangan untuk mengetahui bagaimana proses produksi program Khazanah Trans7. Hasil dari observasi, wawancara, dan dokumentasi dalam penelitian ini dapat disimpulkan bahwa program Khazanah Trans7 episode Khazanah Etalase memiliki format program magazine yang bersifat heterogen. Untuk proses praproduksi, reporter mencari tema lalu mempresentasikan pitching kemudian menuliskan naskah. Pada proses produksi naskah diubah menjadi audio visual dimulai dari visual pitching, syuting, pengiriman gambar, pengeditan naskah dan voice over. Setelah itu ada praproduksi yaitu proses final yang mengabungkan seluruh material sebelum ditayangkan, dengan berbagai proses seperti pengeditan gambar dan voice over, titling, mixing, review, quality control, dan mastering sehingga kemudian siap untuk ditayangkan